CALIFORNIA MASTITIS TEST AND IDENTIFICATION OF ANTIBIOTIC-RESISTANT BACTERIA ON DAIRY CATTLE IN "KUD” SEMEN GANDUSARI SUBDISTRICT, BLITAR - RAHMAHANI, JOLA; Puspitasari, Yulianna; Suwarno (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Mastitis is an inflammation of the udder that often affects dairy cows in the production phase. The impact of mastitis losses is quite large, including a drastic decrease in milk quantity and quality. Mastitis can be caused by antibiotic-resistant bacteria in dairy cows, including Escherichia coli, Staphylococcus spp or Streptococcus spp. The results of a recent study stated that the prevalence of mastitis in Indonesia reached 83%. The Coliform Mastitis Test (CMT), used worldwide for early detection of mastitis, has a specificity of 80.6% and a sensitivity of 82.4%. Semen Village Unit Cooperative (KUD) is a cooperative that is the center of milk production in Blitar District, which accommodates the milk of dairy cows from smallholder farms in Blitar District. The high incidence of mastitis caused by the presence of bacteria resistant to antibiotics encourages counseling on mastitis and identifying bacteria that cause antibiotic resistance. Extension activities are carried out by presenting material about mastitis caused by the presence of bacteria resistant to antibiotics with lecture techniques (PowerPoint slides), videos, questions, and answers, and demonstrating the California Mastitis Test on milk samples as an early detection test, as well as identifying bacteria that cause antibiotic resistance. This series of counseling activities is an effort to reduce the incidence of mastitis through increased knowledge and understanding of the community.